Strategi Peningkatan Pendapatan Sektor Pariwisata di Provinsi Jambi - Amalia, Vera; Anggun Sari, Deby; Pangestu Primadiva, Parassela; Irawan, Deki (Dinasti Review Publisher, 2023)
The increase in the number of tourists to Jambi Province cannot be separated from the role of the government which has declared Jambi Province as a tourist area, in Jambi Province, there are tourist attractions like today. At that time the tourism sector had become an economic source for the people of Jambi Province. This study aims 1) to analyze the development of tourism sector revenue, GRDP, number of tourists, and investment in Jambi Province during the 2000-2021 period. 2) Analyze the contribution of the tourism sector to GRDP in Jambi Province for the 2000-2021 period. 3) Analyze the factors affecting the income of the tourism sector in Jambi Province during the 2000-2021 period. 4) Analyze the strategy of increasing tourism revenue in Jambi Province. By using the dependent variable tourism sector revenue and GRDP variables, the number of tourists and investment. With the results of the regression results using multiple regression it is proven that all independent variables, namely: GRDP, the number of tourists and investment have a significant effect on the dependent variable of tourism sector revenue as a whole.